2022
DOI: 10.1172/jci.insight.155236
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IL-36 improves age-related coronary microcirculatory dysfunction and attenuates myocardial ischemia/reperfusion injury in mice

Abstract: Following myocardial infarction (MI), elderly patients have a poorer prognosis than younger patients, which may be linked to increased coronary microvessel susceptibility to injury. Interleukin-36 (IL-36), a newly discovered proinflammatory member of the IL-1 superfamily, may mediate this injury, but its role in the injured heart is currently not known. We first demonstrated the presence of IL-36(α/β) and its receptor (IL-36R) in ischemia/reperfusion-injured (IR-injured) mouse hearts and, interestingly, noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…CMD mouse models were established using C57BL/6J mice, and the detailed steps are as follows. 28 Firstly, mice were anesthetized with avertin intraperitoneally. Then, they were intubated using a direct visual tracheal intubation puncture cannula, followed by connecting to a small animal ventilator to adjust the frequency and tidal volume.…”
Section: Methodsmentioning
confidence: 99%
“…CMD mouse models were established using C57BL/6J mice, and the detailed steps are as follows. 28 Firstly, mice were anesthetized with avertin intraperitoneally. Then, they were intubated using a direct visual tracheal intubation puncture cannula, followed by connecting to a small animal ventilator to adjust the frequency and tidal volume.…”
Section: Methodsmentioning
confidence: 99%
“…As well as amplifying IL-1 effects, IL-36 is also a mediator of inflammation in its own right. Indeed, its critical role in psoriasis, equalling if not surpassing that of IL-1, is well established with emerging roles in Crohn disease and rheumatoid arthritis recently identified ( 130 132 ). Research into IL-36 as a pro-inflammatory cytokine in various inflammatory diseases is extensive, but studies in AMI or COPD are more recent.…”
Section: Therapeutic Strategies For Targeting Inflammation In Ami And...mentioning
confidence: 99%
“…Further, mCBS injection 5 min before and after cutaneous I/R can consistently and significantly increase the area of skin flap survival (124). IL-36 receptor antagonist (IL-36Ra), encoded by Il36rn, attenuates myocardial IRI though reducing neutrophil recruitment and improving blood flow in mice (181). Tanaka et al (129) found that in Il36rn -/mice, cutaneous I/R resulted in a significant delay in wound healing and increased inflammatory cell infiltration.…”
Section: Extracellular Traps In Cutaneous Ischemia Reperfusion Injurymentioning
confidence: 99%